Let your students cheat on mathematics online exams: students’ perspectives - Nurdin, Erdawati; MZ, Zubaidah Amir; Nufus, Hayatun; Thakur, Deepti; Shah, Firdous A.; Dube, Rakesh; Wijaya, Tommy Tanu (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
The Covid-19 outbreak has an impact on the provision of education. One of them is the process of online assessment or examination. Difficulties occur during online exams; weak supervision can increase cheating behavior among students. Generally, teachers or lecturers think about how to prevent this behavior. However, what if they are allowed to "cheat" on the exam? What do they think? This paper discusses students' perceptions when they were allowed to access various sources during online math exams. What benefits do they get?. The survey was conducted on 78 students of the Mathematics Education Study Program of UIN Sultan Syarif Kasim Riau. The data obtained through a questionnaire were analyzed descriptively. The results of the descriptive analysis showed that the students gave a positive response. The results of this study are expected to be a positive view of the weakness of supervision during online math exams, an idea/way to prevent cheating. In its application, both online learning and assessment, it is necessary to strengthen the character and self-concept of students.